The epidemiology of non-suicidal self-injurious behavior, a non-systematic narrative review - E. V. Darin; O. G. Zaitseva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
Non-suicidal self-injury, as a type of auto-aggression, is a widespread behavioral problem among adolescents. Researchers have noted an increase in the number of self-harm in recent years. The aim of the work: to conduct a narrative review of the scientific literature on the epidemiology of auto-aggression and non-suicidal self-injurious behavior. Method: the article presents a narrative review of domestic and foreign literature on the epidemiology of non-suicidal self-injurious behavior (NSSI). Articles were selected and analyzed in the databases MEDLINE/PubMed, Elibrary.ru, Scopus. To obtain basic information, publications from 2015 to 2022 were used, in international medical journals, as well as relevant references in the reference lists of the analyzed sources. At the same time, early publications on the subject were included for general information, definitions, and historical hindsight. The search was conducted using various variations of the specified keywords.Results: NSSI is most common in adolescents and young adults, and the age of onset has been reported to be most common between 12 and 14 years of age. There is no unambiguously accurate estimate of the prevalence of NSSI, when studying the literature, the prevalence is estimated to be in a wide range from 7.5 to 46.5% among adolescents. According to foreign meta-analyses, at present the average percentage of adolescents who have resorted to self-harm is from 16.9% to 19.5% and tends to increase. The prevalence of the phenomenon has increased greatly with the onset of the Covid-19 pandemic. Conclusion: Auto-aggressive behavior, self-injurious behavior, and non-suicidal self-harm are now common among adolescents. It should be noted that the prevalence rates of this phenomenon remain insufficiently studied and are presented by studies for Western countries, there is still a lack of data in studies of the adolescent population of the Russian Federation due to the low level of knowledge of the phenomenon in the country.